2023
DOI: 10.1101/2023.01.28.526044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Axonal transport of autophagosomes is regulated by dynein activators JIP3/JIP4 and ARF/RAB GTPases

Abstract: Neuronal autophagosomes, "self-eating" degradative organelles, form at presynaptic sites in the distal axon and are transported to the soma to recycle their cargo. During transit, autophagic vacuoles (AVs) mature through fusion with lysosomes to acquire the enzymes necessary to breakdown their cargo. AV transport is driven primarily by the microtubule motor cytoplasmic dynein in concert with dynactin and a series of activating adaptors that change depending on organelle maturation state. The transport of matur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 108 publications
0
6
0
Order By: Relevance
“… 23 Our group recently found that overexpression of GTP-locked ARF6 Q67L did not affect axonal AV transport in WT rat hippocampal neurons, but expression of GDP-locked ARF6 T27N decreased retrograde motility of axonal AVs, supporting a key role for ARF6 in the regulation of AV transport. 38 Notably, while JIP3/4 levels were increased on AVs isolated from mice expressing hyperactive LRRK2, ARF6 levels were not. 10 We hypothesized that ARF6 levels become limiting in the presence of hyperphosphorylated RABs and that overexpression of GTP-ARF6 may restore retrograde AV motility by counterbalancing the abnormally increased levels of JIP3/4 on the AV membrane (depicted in cartoon in Figure 5A ).…”
Section: Resultsmentioning
confidence: 98%
“… 23 Our group recently found that overexpression of GTP-locked ARF6 Q67L did not affect axonal AV transport in WT rat hippocampal neurons, but expression of GDP-locked ARF6 T27N decreased retrograde motility of axonal AVs, supporting a key role for ARF6 in the regulation of AV transport. 38 Notably, while JIP3/4 levels were increased on AVs isolated from mice expressing hyperactive LRRK2, ARF6 levels were not. 10 We hypothesized that ARF6 levels become limiting in the presence of hyperphosphorylated RABs and that overexpression of GTP-ARF6 may restore retrograde AV motility by counterbalancing the abnormally increased levels of JIP3/4 on the AV membrane (depicted in cartoon in Figure 5A ).…”
Section: Resultsmentioning
confidence: 98%
“…Data are available in the article itself, the supplementary materials, and in the public repository Zenodo ( Cason and Holzbaur, 2023 ).…”
Section: Data Availabilitymentioning
confidence: 99%
“…This finding is intriguing because RILP is also a shared effector for Rab7 35 . Additionally, several other proteins have been previously identified, such as TMEM55B 107 , JIP3/JIP4 107 , 108 , SEPT9 109 , and TRPML1 110 , that facilitate the coupling of lysosomes to dynein. Furthermore, findings from studies conducted in Drosophila have demonstrated that Arl8 has the ability to interact with the ortholog of RILP 48 .…”
Section: Discussionmentioning
confidence: 99%